Investigation of the bonding characteristics of termite hill clay in Akure, Ondo State, Nigeria for use in foundries (2018)
On annual basis, the activities of termites to man’s habitat have been found to be destructive. Interestingly, man still goes in search of these insects day-in-day-out because of their usefulness in making life more convenient. In this work, the bonding characteristics of an active termite hill clay in the as – received state have been investigated. Three (3) different layers of clay: (Outermost layer -TCH 1; middle layer -TCHM 1 and innermost layer -TQH 1) from a termite colony were separately collected from a forest settlement in Akure, Nigeria, prepared and analyzed by means of compressive strength testing using an Instron Universal tester and mineralogical composition characterization using X-ray mini diffractometer. While results of the compressive strength testing showed that TQH 1, the innermost layer withstood the maximum compressive load of 3,370.27612N and absorbed 51.56948J in the process, results from the mineralogical composition characterization revealed that TQH 1 contained Sillimanite which melts around 1,850°C. This work is of paramount importance to the use of locally available materials, and in large quantities in Nigeria at little or no cost. This has implication for the development of foundries and foundry activities in order to meet up with the increasing demands of the foundry.